Pentingnya Peran Guru Di Sekolah Dalam Pembentukan Karakter Siswa Di Era Digital - annisa filaidi; Neviyarni; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2023)
The author's goal of conducting this research is the rampant problems that the author sees in developing student character in this digitalization era. What we know is that with this digitalization era, all aspects and information, both useful and information that is not easily accessible to students, therefore the sophistication of this digitalization era has a negative impact on student behavior. With this change, the role of the teacher is very large. How should teachers be able to provide direction to students regarding this digitalization era. Research qualitative descriptive model researchers use for this study by using document analysis techniques where the author collects articles or journals that are relevant to the topic raised by the researcher. Based on the data analysis that the writer did, it was found that the role of the teacher is so big in managing student personality. The teacher's task is not only to provide explanations and process values ​​from student learning outcomes, the teacher is also responsible for designing and carrying out teaching and learning activities. In this regard, teachers should be professional, intelligent, attentive and skilled teachers in carrying out their work, because most of the success of students depends on their respective teachers.